Plasma Big Endothelin-1 Level Predicted 5-Year Major Adverse Cardiovascular Events in Patients With Coronary Artery Ectasia - Zhongxing Cai (Frontiers Media S.A., 2021)
Background: Coronary artery ectasia (CAE) is found in about 1% of coronary angiography and is associated with poor clinical outcomes. The prognostic value of plasma big Endothelin-1 (ET-1) in CAE remains unknown.Methods: Patients with angiographically confirmed CAE from 2009 to 2015, who had big ET-1 data available were included. The primary outcome was 5-year major adverse cardiovascular events (MACE), defined as a component of cardiovascular death and non-fatal myocardial infarction (MI). Patients were divided into high or low big ET-1 groups using a cut-off value of 0.58 pmol/L, according to the receiver operating characteristic curve. Kaplan-Meier method, propensity score method, and Cox regression were used to assess the clinical outcomes in the 2 groups.Results: A total of 992 patients were included, with 260 in the high big ET-1 group and 732 in the low big ET-1 group. At 5-year follow-up, 57 MACEs were observed. Kaplan-Meier analysis and univariable Cox regression showed that patients with high big ET-1 levels were at increased risk of MACE (9.87 vs. 4.50%; HR 2.23, 95% CI 1.32–3.78, P = 0.003), cardiovascular death (4.01 vs. 1.69%; HR 2.37, 95% CI 1.02–5.48, P = 0.044), and non-fatal MI (6.09 vs. 2.84%; HR 2.17, 95% CI 1.11–4.24, P = 0.023). A higher risk of MACE in the high big ET-1 group was consistent in the propensity score matched cohort and propensity score weighted analysis. In multivariable analysis, a high plasma big ET-1 level was still an independent predictor of MACE (HR 1.82, 95% CI 1.02–3.25, P = 0.043). A combination of high plasma big ET-1 concentrate and diffuse dilation, when used to predict 5-year MACE risk, yielded a C-statistic of 0.67 (95% CI 0.59–0.74).Conclusion: Among patients with CAE, high plasma big ET-1 level was associated with increased risk of MACE, a finding that could improve risk stratification.